La cadena perpetua en casos de violación y asesinato de menores, en Ecuador y en América Latina. - Hermida Medina, Andrea Paola (2022)
This study presents an analysis of life imprisonment in cases of rape and murder of minors in Ecuador and Latin America. Because, over the years there has been an increase in the number of murders and rapes of minors, consequently, there is a concern to implement legislative measures to protect the physical, psychological, and sexual integrity of children and adolescents. Through the strengthening of the criminal legal system, which is why some Latin American countries have decided to implement the penalty of life imprisonment in their legislation. Therefore, this thesis was developed with the main objective of analyzing life imprisonment in cases of rape and murder of minors in Ecuador and Latin America, to determine the convenience of its adoption in Ecuadorian legislation. A qualitative, analytic, and synthetic bibliographic, and descriptive documentary methodology was used, and the interview technique was applied to judges and prosecutors of the Riobamba canton. The development of the theoretical perspective was based mainly on the review of documentation on the legislation of some Latin American countries in favor and against life imprisonment, as well as international conventions and treaties. This research found that Ecuador is not legally prepared to adopt this article of liberty deprivation, because it has been subscribed to international treaties that seek the reintegration of the prisoner into society, and the Constitution of the Republic of Ecuador prohibits cruel, inhuman or degrading treatment. Additionally, it was determined that the increase in judgments does not reduce the rate of crimes committed, since there is no a reasonable justification for the implementation of life imprisonment.